2009
DOI: 10.1111/j.1600-0501.2008.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation with various bone graft substitutes in critical‐sized rat calvarial defect

Abstract: N-HA was an osteoconductive bone substitute for treating osseous defects in critical size defects of rat calvaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 32 publications
4
46
0
6
Order By: Relevance
“…The ability of Bio-Oss to facilitate bone regeneration has also been evaluated in numerous animal studies using criticalsize defects and domes 8,9,11,22,[25][26][27]30,35,36,[38][39][40][41]43,44,48 . Bone healing in the maxillary sinus, artificial defects, and domes may not be directly comparable but a number of similar characteristics have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Bio-Oss to facilitate bone regeneration has also been evaluated in numerous animal studies using criticalsize defects and domes 8,9,11,22,[25][26][27]30,35,36,[38][39][40][41]43,44,48 . Bone healing in the maxillary sinus, artificial defects, and domes may not be directly comparable but a number of similar characteristics have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was based on data from one study evaluating the effect of various bone substitute material in bone regeneration in CSD in rats, using a similar histomorphometric evaluation [33]. In this study, the minimum average difference in bone formation observed among the various biomaterials was 7.3%, with a standard deviation of…”
Section: Statisticsmentioning
confidence: 99%
“…The Norian presented superior space maintaining abilities compared to ChronOs and BonePlast. The V v s of new bone were similar between the materials studied and comparable to the unfilled controls, described, for example, by Park et al (2009), and lower of the V v of Bio-oss, hydroxy apetite and calcium sulfate hydroxyl apetite filled defects in the same study, although the last were studied earlier, in week 12 [14]. This points that the described mod is feasible and promising, other new bone substitutes that can be injected need to be sought.…”
Section: Discussionmentioning
confidence: 64%